1978
DOI: 10.1007/bf02906508
|View full text |Cite
|
Sign up to set email alerts
|

The pachytene karyotype of Schizophyllum commune analyzed by three dimensional reconstruction of synaptonemal complexes

Abstract: Three dimensional reconstructions of 15 pachytene nuclei of Schizophyllum commune have revealed in each nucleus I 1 distinct synaptonemal complexes, demonstrating a haploid chromosome number of 11. Each bivalent contained one short region of condensed chromatin marking the position of the centromere. The synaptonemal complex of each bivalent contained from 0 to six recombination nodules. A high correlation was found between the total length of the synaptonemal complexes in a nucleus and the number of recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…This study recorded a 1 .8x range of SC lengths among pachytene oocytes and also concluded that SC lengths initially decreased during early to mid pachytene before extending again during late pachytene. A similar pattern of change in SC length was described in hamster spermatocytes, where sub-stages of pachytene Carmi et al (1978) were defined by changes in XY morphology (Moses et a!., 1977 (Gillies, 1983). The ranges of SC lengths observed in Crepis capillaris are similar to those described in maize which supports the contention that the pachytene nuclei analysed in the present study represent the entire range of pachytene.…”
Section: Introductionsupporting
confidence: 55%
“…This study recorded a 1 .8x range of SC lengths among pachytene oocytes and also concluded that SC lengths initially decreased during early to mid pachytene before extending again during late pachytene. A similar pattern of change in SC length was described in hamster spermatocytes, where sub-stages of pachytene Carmi et al (1978) were defined by changes in XY morphology (Moses et a!., 1977 (Gillies, 1983). The ranges of SC lengths observed in Crepis capillaris are similar to those described in maize which supports the contention that the pachytene nuclei analysed in the present study represent the entire range of pachytene.…”
Section: Introductionsupporting
confidence: 55%
“…These studies have shown that at pachytene, homologous chromosomes are held in register by a continuous synaptonemal complex from telomere to telomere revealing an apparently specific site-to-site matching of homologous regions. Both light and electron microscopical studies agree in that the number of irregularities is surprisingly low (2,4,6,9,13,14,16,22,33). Furthermore, it has been demonstrated that prior to the onset of pairing, homologous chromosomes are either located at random in the nucleus (1 i, 12, 22, 25) or in separate nuclei (4, 0105-1938/79/0044/0101/$ 05.00 32, 33) the only exception being organisms with a permanent somatic pairing of homologous chromosomes.…”
Section: Introductionmentioning
confidence: 70%
“…It is the impression, however, that nodules at early pachytene are larger, denser and more frequently positioned adjacent to the central region of the complex than those of early zygotene nuclei. Comparable intranuclear variation in the morphology of the nodules has been described in Ascomycetes and Basidiomycetes (3,15,53). In Neurospora, for example, the length of the nodules ranges from 55 to 210 nm and the width from 20 to 90 nm.…”
Section: Morphologymentioning
confidence: 81%
“…The material consists of biopsies from three normal fertile men undergoing vasectomy. A detailed description of the mid-late pachytene stage in the spermatocytes of these men has been presented in a previous publication (cases [3][4][5]20). In addition, a testicular biopsy from a man carrying a balanced translocation was analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation